Глобально-локальний метод для сегментації та аналізу зображень зерен металів - Кобасяр, М.І.; Корній, В.В.; Косаревич, Р.Я.; Русин, Б.П. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
The method for automation of the image segmentation of the metal grains and estimation of their characteristics was offered. The aim of the application is to assist the experts in locating of potentially grain cases for further analysis. The researches are carried out on different types of grains to approve the correctness of the proposed approach.